2000
DOI: 10.1128/jvi.74.8.3449-3454.2000
|View full text |Cite
|
Sign up to set email alerts
|

Virus Load and Sequence Variation in Simian Retrovirus Type 2 Infection

Abstract: The natural history of type D simian retrovirus (SRV) infection is poorly characterized in terms of viral load, antibody status, and sequence variation. To investigate this, blood samples were taken from a small cohort of mostly asymptomatic cynomolgus macaques (Macaca fascicularis), naturally infected with SRV type 2 (SRV-2), some of which were followed over an 8-month period with blood taken every 2 months. Provirus and RNA virus loads were obtained, the samples were screened for presence of antibodies to SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…The findings seen in subject 1 are consistent with data obtained from macaques that are naturally infected with SRV (18,20,29). SRV infection in macaques is thought to result in persistent infection, although SRV may become latent in the face of a vigorous immune response (18).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings seen in subject 1 are consistent with data obtained from macaques that are naturally infected with SRV (18,20,29). SRV infection in macaques is thought to result in persistent infection, although SRV may become latent in the face of a vigorous immune response (18).…”
Section: Discussionsupporting
confidence: 82%
“…Spouses of both persons were unavailable for testing to determine whether this SRV seroreactivity is transmissible to humans, and while the absence of disease in both subjects is reassuring, our information is limited by the small sample size, the relatively short length of follow-up, and the absence of clinical observations coincident with infection and seroconversion. However, the anti-SRV neutralizing-antibody titers seen in both seropositive persons may offer them some degree of immunologic protection from viremia and subsequent disease manifestation, as has been recently observed in SRV-2-infected macaques with similar antibody titers and low or undetectable viral loads (29).…”
Section: Discussionmentioning
confidence: 69%
“…ELISA data for these three animals indicated that serological responses and viremia are inversely related, as previously noted (15,28). 977G had a minimal antibody response against SRV, whereas 540FC and 963DBDA had strong antibody responses.…”
Section: Discussionsupporting
confidence: 79%
“…Most importantly for diagnostic purposes, the LTR assay detected all viremic animals. It is interesting that almost half of the viremic animals in the cross-sectional study were env assay negative (env PCR assays designed to detect alternative serogroups, SRV-1 and SRV-3, also failed to amplify any sequence in DNA from one such individual); we propose that minor variation in the SRV env sequence of virus of serogroup 2, as has been reported previously (18,28), could account for this. Viremia and virus replication would be expected to result in the generation of more sequence variants.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, one yet-to-be-proved mechanism of morphine-mediated up-regulation of CCR5 is through the down-regulation of chemokine synthesis. SRV are endemic in wild macaques of India and Indonesia and in captive macaques important for medical research (33). Five distinct neutralization serotypes (SRV1-SRV5) have been described, of which three have been molecularly cloned (SRV1-SRV3).…”
Section: Infection Of Cem X174 Cells With Sivmac239 or Srv-methodsmentioning
confidence: 99%